(untitled) (Journal of the Sociology and Theory of Religion, 2026)
Our objective is to study the phenomenon of religious conversion as one of the social realities that occur in our society and that often goes unnoticed in sociological studies. It is an anthropological question and we approach it from a qualitative methodological strategy to delve into a fact that can be studied from the techniques of social science. We investigate what happens in the life of a young person for an event of such relevance to arise in the midst of a secularized society. It supposes for the subjects a radical change of life that is not always fully understood.